"Contact A Family": professionals and parents in partnership. Issue 10 (21st September 2005) - Davies, S; Hall, D
Abstract : This paper considers the evidence base on the role of parent organisations in meeting the needs of parents of disabled children for information and support. Having a disabled child is a major cause of stress and has an impact on the health and wellbeing of the entire family. Current concepts of stress and coping are used to consider coping strategies, including the search for information, the desire to stay in control, and the quest for social support. How and when information and support are provided will impact on how well the family adjust and cope.